Contrast-enhanced ultrasound determines supraspinatus muscle atrophy after cuff repair and correlates to functional shoulder outcome - Fischer, Christian; Groß, Sascha; Zeifang, Felix; Schmidmaier, Gerhard; Weber, Marc-André; Kunz, Pierre (The American journal of sports medicine, 2018)
Background:Muscle degeneration as a consequence of rotator cuff tears is mainly assessed by magnetic resonance imaging. Contrast-enhanced ultrasound (CEUS) is a new functional imaging method to assess microvascular perfusion as a fundamental parameter of muscle tissue vitality. In this cross-sectional study, the authors evaluated supraspinatus muscle perfusion after cuff repair and analyzed its association with functional shoulder outcome and the grade of echogenicity in B-mode ultrasound indicating fatty infiltration.Hypothesis:The authors expected reduced microperfusion of the operated versus the contralateral supraspinatus muscle and a correlation of the muscular microperfusion with functional shoulder outcome.Study Design:Cross-sectional study; Level of evidence, 3.Methods:Patients who received unilateral repair of the supraspinatus tendon between 2009 and 2014 were invited for a single follow-up examination. Functional scores were assessed, including the Constant-Murley score and American Shoulder and Elbow Surgeons score. CEUS examination was performed bilaterally in an oblique sagittal plane of the supraspinatus fossa. Perfusion was quantified by the parameters wash-in perfusion index (WiPI) and peak enhancement via VueBox quantification software. The results of the Constant-Murley score, American Shoulder and Elbow Surgeons score, and perfusion parameters were referenced to the contralateral shoulder. Echogenicity of the supraspinatus muscle was classified with a 3-point scale as compared with the trapezius muscle.Results:Sixty-seven patients were available, with a mean follow-up of 38.0 ± 18.5 months. Functional assessment showed impaired shoulder function on the operated shoulder as compared with the contralateral side (relative Constant Score [CS], 80% ± 19%). CEUS revealed diminished perfusion on the operated shoulder (WiPI, 55.1% ± 40.2%, P < .001). A strong correlation could be demonstrated between the perfusion deficit and functional impairment (relative WiPI and CS: rs = .644, P < .001). Higher grade of echogenicity in B-mode ultrasound was associated with reduced perfusion.Conclusion:CEUS could visualize impaired supraspinatus muscle perfusion after rotator cuff repair as compared with the contralateral, healthy shoulder. With its ability to quantify microvascular perfusion as a surrogate parameter for muscle vitality and function, CEUS may serve as a quantitative method to evaluate rotator cuff muscles.